The development and evaluation of effectiveness of animal derived monovalent antivenom against Macrovipera lebetina obtusa (MLO) venom - A. V. Kishmiryan (ՀՀ ԳԱԱ հրատ.)
TThe article describes the processing and development of animal-derived monovalent antivenom against MLO venom according to several protocols, which is a significant problem for public health and the Ministry of Health of Armenia. The developed product is already showing quite high effectiveness and after several experiments, it will be possible to derive the antivenom satisfying international standards which will be much cheaper and accessible compared with Market rivals. Հոդվածում նկարագրված է մի շարք պրոտոկոլների համադրությամբ MLO օձի թույնի դեմ կենդանական ծագման, մոնովալենտ հակաթույնի մշակումը և ստացումը, ինչը բավականին արդիական խնդիր է ներկայիս ՀՀ առողջապահության համար: Ստացված արգասիքը ցուցաբերում է բավականին բարձր արդյունավետություն և որոշակի կլինիկական փորձարկումներից հետո հնարավոր կլինի ստանալ միջազգային ստանդարտներին համապատասխանող բուժամիջոց, որն ավելի մատչելի և հասանելի կլինի մրցակից պատրաստուկներից: В статье описана разработка и получение мoновалентного противоядия животного происхождения против яда змеи MLO с использованием сочетания нескольких протоколов, что является актуальной проблемой для нынешнего здравоохранения РА. Полученный продукт показывает довольно высокую эффективность и уже после определенных клинических испытаний можно будет получить соответствующее международным стандартам лекарственное средство, которое будет более доступным по сравнению с конкурентными препаратами.
Keywords: Biology; Pharmacology